2013
DOI: 10.1007/s40262-013-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmacogenetics in the Disposition of and Response to Tacrolimus in Solid Organ Transplantation

Abstract: The calcineurin inhibitor tacrolimus is the backbone of immunosuppressive drug therapy after solid organ transplantation. Tacrolimus is effective in preventing acute rejection but has considerable toxicity and displays marked inter-individual variability in its pharmacokinetics and pharmacodynamics. The genetic basis of these phenomena is reviewed here. With regard to its pharmacokinetic variability, a single nucleotide polymorphism (SNP) in cytochrome P450 (CYP) 3A5 (6986A>G) has been consistently associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
197
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(208 citation statements)
references
References 177 publications
7
197
1
3
Order By: Relevance
“…[12] Individuals homozygous for the CYP3A5*3 allele are referred to as CYP3A5 non-expressers, whereas individuals carrying at least one CYP3A5*1 allele are known as CYP3A5 expressers. The reduced enzymatic activity associated with the CYP3A5*3 allele has been associated with a reduced Tac dose requirement (for a review, see reference [13]). CYP3A5 expressers require a Tac dose that is about 50% higher than that of CYP3A5 non-expressers to reach the same exposure.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…[12] Individuals homozygous for the CYP3A5*3 allele are referred to as CYP3A5 non-expressers, whereas individuals carrying at least one CYP3A5*1 allele are known as CYP3A5 expressers. The reduced enzymatic activity associated with the CYP3A5*3 allele has been associated with a reduced Tac dose requirement (for a review, see reference [13]). CYP3A5 expressers require a Tac dose that is about 50% higher than that of CYP3A5 non-expressers to reach the same exposure.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…Some clinical factors and genetic factors play critical roles in determining TAC pharmacokinetics (PK) [9][10][11] . Tacrolimus is known to be transported by P-glycoprotein (MDR1 or ABCB1) and metabolized by cytochrome P450 (CYP) 3A4 and CYP3A5.…”
Section: Introductionmentioning
confidence: 99%
“…The controversy in the results concerning the long-term adverse effects of Tac prompted an assessment of the contribution of CYP 3A5 and ABCB1 polymorphisms on renal function parameters in transplant recipients in the present study. The majority of the previous studies found no correlation between investigated polymorphisms and the clinical features of Tac toxicity or renal function attenuation (6,8,31). The bivariate linear regression showed that CYP 3A5 polymorphism, but not ABCB1 polymorphism, independently affects renal function from 6 to 24 months after renal transplantation (Table V).…”
Section: Discussionmentioning
confidence: 91%
“…The ABCB1 gene is also polymorphically expressed with ≥50 different polymorphisms known to date. In contrast to CYP 3A5, neither of the ABCB1 polymorphisms leads to complete loss of the PGP function (5,8). The most studied ABCB1 gene polymorphism is 3435C>T, which includes a C to T transition at position 3435 within exon 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation